2019
DOI: 10.1007/s00198-019-05234-w
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on skeletal health in inflammatory bowel disease

Abstract: Osteopenia and osteoporosis are common features in inflammatory bowel disease (IBD), comprising both Crohn's disease and ulcerative colitis. Moreover, Crohn's disease is associated with increased fracture risk. The etiology of bone loss in IBD is multifactorial. It includes insufficient intake or absorption of calcium, vitamin D, and potassium; smoking; a low peak bone mass; a low body mass index; and decreased physical activity. In several studies, it has been shown that elevated concentrations of systemic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…Moreover, studies estimated that as many as 77% of patients with IBD have osteopenia and 12–41% have osteoporosis [ 41 , 45 ]. The risk of osteoporosis and osteopenia among patients with IBD is also related to insufficient intake and absorption of calcium and potassium, lower body mass index (BMI) and insufficient physical activity, low peak bone mass, and certain medications, especially glucocorticosteroids [ 46 , 47 ]. Adequate calcium intake is crucial due to IBD’s association with an increased incidence of osteoporosis, and additionally, during ongoing inflammation, pro-inflammatory cytokines affect the activity of bone cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies estimated that as many as 77% of patients with IBD have osteopenia and 12–41% have osteoporosis [ 41 , 45 ]. The risk of osteoporosis and osteopenia among patients with IBD is also related to insufficient intake and absorption of calcium and potassium, lower body mass index (BMI) and insufficient physical activity, low peak bone mass, and certain medications, especially glucocorticosteroids [ 46 , 47 ]. Adequate calcium intake is crucial due to IBD’s association with an increased incidence of osteoporosis, and additionally, during ongoing inflammation, pro-inflammatory cytokines affect the activity of bone cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PTH/Pth1r, PI3K-Akt, NF-κB, and other signaling pathways were also mediated by m6A, which is important in the regulation of bone homeostasis. Roux, 2015;van Bodegraven and Bravenboer, 2019). Estrogen deficiency also increases inflammatory cytokines (Tsangari et al, 2004), followed by the activation of osteoclasts, increased bone resorption, and osteoporosis (Chen et al, 2017).…”
Section: Regulating M6a Methylation On Osteoclastsmentioning
confidence: 99%
“…The mechanism leading to low BMD and increased fracture risk caused by inflammatory bowel disease is closely related to OPG/RANKL/RANK pathway. In several studies, it has been shown that inflammatory bowel disease results in increased concentrations of proinflammatory cytokines, including tumor necrosis factor alpha (TNF- α ), interleukin (IL)-1 β , IL-6, and IL-17 [ 34 ]. It is well known that cytokines such as TNF- α , IL-1 β , and IL-6 increase the production of receptor activator of nuclear factor kappa B ligand (RANKL) by preosteoblasts, thereby promoting osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%